Correlation of finger-to-floor distance with the spinal mobility, spinal function indices and initial determination of its optimal cutoff value: a multicentre case–control study - Guo, Genggeng; Zhang, Yulu; Lin, Diantian; Chen, Zhihan; Yan, Qing; Gao, Fei; Wu, Yanfang; He, Juanjuan; Chen, Da; Xie, Zugang; Huang, Feng; Zhang, Shengli (Frontiers in Medicine, 2023)
Objective To identify the correlation between finger-to-floor distance(FFD) and the spinal function indices and disease activity scores of ankylosing spondylitis (AS) via a multicentre case–control study, and to calculate the optimal cutoff value of FFD using statistical methods. Methods Patients with AS and healthy individuals were recruited, and the FFD and other spinal mobility values were measured. The correlation between the FFD and the Bath Ankylosing Spondylitis Metric Index (BASMI), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI) was analyzed using Spearman rank correlation analysis. Receiver operating characteristic (ROC) curves of FFD stratified by gender and age were drawn and their optimal cutoff values were determined. Results A total of 246 patients with AS and 246 healthy subjects were recruited. The FFD was strongly correlated with BASMI (r = 0.72, p < 0.001), moderately correlated with BASFI (r = 0.50, p < 0.001) and weakly correlated with BASDAI (r = 0.36, p < 0.001). The lowest cutoff value of the FFD was 2.6 cm while the highest was 18.4 cm. Moreover, the FFD was significantly correlated with sex and age. Conclusion There exists a strong correlation between the FFD and spinal mobility, a moderately correlation and function, which provides reliable data for the evaluation of patients with AS in clinical settings and the rapid screening of low back pain-related diseases in the general population. Furthermore, these findings have clinical potential in improving the missed diagnosis or delayed diagnosis of low back pain.